STRATEGI PELAKSAAN PEMBELAJARAN SENI RUPA BERBASIS TAKSONOMI VARIABEL PEMBELAJARAN DI SMPN 1 PENDOPO BARAT, SUMATERA SELATAN - Sutra, Dr. Ramalis Hakim, M.Pd., Dra. Jupriani, M.Sn. (Serupa The Journal of Art Education, 2019)
The purpose of this study was to find out how the strategy of implementing artlearning in West Pendopo 1 Public Middle School. This research is qualitative in the form of qualitative with the presentation of descriptive data, in this study, researchers were present at the study site to obtain data through observation and interviews regarding the learning process of Fine Arts directly from the research site at West Pendopo 1 Public High School. The data obtained came from teachers who taught cultural arts and the principal of the West Pendopo 1 Junior High School in Muara Lintang Village, West Pendopo, East Java Lawang. Based on the focus of the problem under study is the implementation of art learning. Then the verbal data is taken from the sources through interview techniques and visual documentation in the form of photos from the implementation of art learning. Data analysis techniques are by reducing, carrying out data displays, and drawing conclusions. The findings of the study show that 1) The taxonomy of the learning method variable in the field of teaching strategy has gone well enough where the teacher prepares the lesson plan first and implements learning in accordance with the lesson plan made. 2) The implementation of strategies for delivering art teaching in SMP N 1 West Pendopo still uses simple media due to limited facilities. 3) Implementation of management of fine arts learning at West Pendopo 1 Junior High School at the beginning of learning teachers carry out activities that can increase student motivation and to measure learning progress teacher students give tests at the end of learning material. Then from that it can be concluded that the implementation of art learning in the form of the West Pendopo 1 Junior High School, it had run quite wellKeywords: Learning taxonomy of variables, Organizing learning, Presenting learning, managing learning, Organizing learning.